Fludrocortisone in the treatment of hypotensive disorders in the elderly. - Hussain, R. M. (1996)
OBJECTIVE: To evaluate tolerance of fludrocortisone in older patients with hypotensive disorders. DESIGN: Prospective case series. SETTING: Syncope clinic. PATIENTS: 64 Consecutive patients over 65 years (mean age 80 years) with one or more hypotensive disorders (orthostatic hypotension, vasodepressor carotid sinus syncope, and/or vasodepressor neurocardiogenic syncope. INTERVENTIONS: Fludrocortisone in daily doses of 100 micrograms [corrected] (72%), 50 micrograms [corrected] (27%), and 200 micrograms [corrected] (one patient). MAIN OUTCOME MEASURES: Adverse events, treatment withdrawal. RESULTS: During follow up 13 patients died of unrelated causes. Of the remainder 33% discontinued fludrocortisone at a mean of five months. Reasons for discontinuing treatment were hypertension, five; cardiac failure, four; depression, three; oedema, three; and unspecified, two. In those who continued treatment supine systolic and diastolic blood pressure did not differ significantly from baseline (follow up two to 21 months). Hypokalaemia developed in 24% at a mean of eight months; in no case was treatment withdrawn because of hypokalaemia. CONCLUSION: Fludrocortisone, even in low doses, is poorly tolerated in the long term in older patients with hypotensive disorders.